2019
DOI: 10.1007/s10899-018-09825-w
|View full text |Cite
|
Sign up to set email alerts
|

Struggling with Happiness: A Pathway Leading Depression to Gambling Disorder

Abstract: Check the metadata sheet to make sure that the header information, especially author names and the corresponding affiliations are correctly shown.• Check the questions that may have arisen during copy editing and insert your answers/ corrections.• Check that the text is complete and that all figures, tables and their legends are included. Also check the accuracy of special characters, equations, and electronic supplementary material if applicable. If necessary refer to the Edited manuscript.• The publication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
(64 reference statements)
0
10
0
3
Order By: Relevance
“…Research with older adults has also investigated the role of savoring in promoting resilience ( Smith and Hollinger-Smith, 2015 ) and positive attitudes toward aging ( Bryant et al, 2021 ), improving physical health ( Geiger et al, 2017 ), buffering the deleterious effects of illness on subjective well-being ( Smith and Bryant, 2016 ), and lowering cardiovascular reactivity and boosting agency ( Borelli et al, 2020 ). Savoring has also been identified as a resource in bereavement ( Permanadeli and Sundararajan, 2021 ), in lowering suicide risk ( Klibert et al, 2019 ), and in protecting soldiers from the psychological effects of combat exposure ( Sytine et al, 2018 ); and kill-joy thinking has been found to mediate the relationship between depression symptomatology and gambling disorder severity ( Rogier et al, 2019 ). In addition, researchers have used savoring to increase people’s consumption of healthy foods ( Coary and Poor, 2016 ), decrease overeating ( Black and Areni, 2016 ), and promote healthy relationships with food ( Batat et al, 2019 ).…”
Section: Historical Evolution Of the Concept And Measurement Of Savoringmentioning
confidence: 99%
“…Research with older adults has also investigated the role of savoring in promoting resilience ( Smith and Hollinger-Smith, 2015 ) and positive attitudes toward aging ( Bryant et al, 2021 ), improving physical health ( Geiger et al, 2017 ), buffering the deleterious effects of illness on subjective well-being ( Smith and Bryant, 2016 ), and lowering cardiovascular reactivity and boosting agency ( Borelli et al, 2020 ). Savoring has also been identified as a resource in bereavement ( Permanadeli and Sundararajan, 2021 ), in lowering suicide risk ( Klibert et al, 2019 ), and in protecting soldiers from the psychological effects of combat exposure ( Sytine et al, 2018 ); and kill-joy thinking has been found to mediate the relationship between depression symptomatology and gambling disorder severity ( Rogier et al, 2019 ). In addition, researchers have used savoring to increase people’s consumption of healthy foods ( Coary and Poor, 2016 ), decrease overeating ( Black and Areni, 2016 ), and promote healthy relationships with food ( Batat et al, 2019 ).…”
Section: Historical Evolution Of the Concept And Measurement Of Savoringmentioning
confidence: 99%
“…The 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) defines GD as a pattern of repeated gambling associated with great distress and disability [5]. Studies have shown that depressive moods can cause GD to exacerbate and interfere with healing [6,7]. Furthermore, a study has reported that patients with comorbidities accounted for 38% of pathological gamblers who are at a high suicide risk [8].…”
Section: Introductionmentioning
confidence: 99%
“…While the exact cause and effect association between depressive illnesses and GD remains unelucidated, some researchers have concluded that GD could facilitate depression [9]. Furthermore, the severity of GD positively correlates with the seriousness of depression, stress, and anxiety [7]. Therefore, both improving depressive symptomatology and preventing depression may serve as part of the key strategies for alleviating GD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…O TJ tem alta correlação com dependência de substâncias como álcool e drogas Gentil Filho, 2007;Buja et al, 2017) e frequentemente há associação com outros transtornos psiquiátricos tais como depressão e ideação suicida (Rogier;Picci;Velotti, 2019), transtorno de ansiedade e outros transtornos de humor Stinson;Grant, 2005;Cosenza, 2018). Em estudo para analisar os três grupos com hábitos de jogo (TJ, jogo social e jogo em personalidades psiquiátricas), verificou-se que o grupo do TJ possui os maiores índices de comorbidade em comparação aos demais grupos (Parhami et al, 2014).…”
Section: Comorbidades E Relações Genéticas E Bioquímicasunclassified
“…Diversão e motivação financeira podem explicar a decisão inicial de jogar (Rogier;Picci;Velotti, 2019;Eysop et al, 2019); porém, à medida que progride o compromisso com a atividade, o PJ desenvolve crenças e rituais supersticiosos, muitas vezes estereotipados, sedimentados pela experiência acumulada em sucessivas apostas.…”
Section: Desamparo Aprendido Ilusão De Controle E Superstiçãounclassified